INVENTARISASI FASILITAS JALAN UNTUK MENINGKATKAN KAPASITAS JALAN SUNGAI RAYA DALAM KOTA PONTIANAK - Wahyudi, -; Erwan, Komala; Sulandari, Eti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
West Kalimantan Province experienced a rapid development in various fields, especially in transportation. Road is an infrastructure in the mobility of the population in addition to having an important role in supporting the continuity of economic activities, social needs, commerce, culture, defense and so forth. This situation should be accompanied also with the feasibility of construction and road facilities, where roads are the main means of infrastructure on land. Good facilities from the road are needed so as not to impact on the smoothness of its users. Road as one of the infrastructure of land transportation, has the basic function of providing optimum services on traffic flow such as, safe and comfortable to the road users.The analysis is done manually in accordance with the condition of traffic flow in Indonesia. In this case the analysis is done using Manual Capacity of Indonesia 1997 (MKJI 1997) to take into account the capacity and inventory of road facilities. Traffic data obtained from field surveys conducted for 4 days is on Friday, Saturday, Sunday and Monday, date (8,9,10 and 11 on January 2016) for 12 hours presented in the form of vehicle data tables.Based on the results of performance and capacity analysis on Jalan sungai raya Dalam Pontianak by using MKJI method 1997 in the capacity of Jalan sungai Raya Dalam in 2016 that is on Friday, Saturday, Sunday and Monday amounted to 2179.8 smp / hour with the value of DS that occurred on the Jalan Sungai Raya Dalam at 0.618 with service level category